Coordination-Driven Self-Assembly of Silver(I) and Gold(I) Rings: Synthesis, Characterization, and Photophysical Studies - Fulong, Cressa Ria P.; Kim, Sewon; Friedman, Alan E.; Cook, Timothy R. (Frontiers in Chemistry, 2019)
In this work, we investigate the self-assembly between Ag(I) and Au(I) centers and pyridyl donors to form hexagonal metallacycles and related linear complexes. The formation of group 11 metallacycles is motivated by their potential applications in mixed-matrix materials wherein metal ions can interact with substrate to facilitate separations chemistry with reduced energy requirements, in particular the isolation of ethylene and light olefins. Existing processes involve cryogenic distillation, an energy intensive and inefficient method. The precipitation of hexagonal metallacycles upon assembly in chloroform/methanol mixtures results in high solid-state photo-stability. Whereas the Ag(I) species have fast kinetics and high formation constants in acetone, this solvent interferes in the formation of the analogous Au(I) complexes. The photophysical properties of this suite of metallacycles was investigated including steady-state absorption, emission, and time-resolved lifetime measurements. All ligands and hexagons exhibited ligand-centered singlet emissions with ground-state absorption and emission perturbed upon coordination. The ligand-based fluorescent photoluminescence was affected by the heavy-atom effect when halide or metals are present, attenuating quantum yields as evidenced by increases in the experimentally measured non-radiative rate constants.